Regression of Atherosclerotic Damaged Vessels Caused by Drugs and Dietary Factors - o’g’li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2023)
Data from clinical studies on the effect of drugs on the size and density of atherosclerotic plaques in the wall of coronary and cerebral arteries are presented. The phenomenon of regression of atherosclerotic lesions in Leningrad siege survivors during a period of prolonged fasting is analyzed. The effect of angiotensin-converting enzyme inhibitors on apoptosis of smooth muscle and foam cells of atherosclerotic plaque in sanological mechanisms in atherosclerosis is discussed. The concept of natural regression of atherosclerosis and the feasibility of developing ways of its pharmacological activation are formulated.